"Return That Which Does Not Belong to You": Mikhail Shishkin's Borrowings in Maidenhair. Issue 2 (4th March 2019) - VERGARA, JOSÉ
Abstract : Immediately upon its publication in 2005, Mikhail Shishkin's third novel Maidenhair was met with acclaim. However, the author also found himself mired in a controversy that spread from literary magazines to LiveJournal comment sections after poet Alexander Tankov noticed that Shishkin had inserted several passages from Soviet writer Vera Panova's memoirs into his own text without attribution. At the core of the dispute lay a central question: How do we define Shishkin's plagiarism? While some participants in the debate labeled Shishkin's work "parasitic" or "an act of marauding, " others defended him by suggesting that the rules of literature have changed. Overall, however, critics' arguments fail to take Shishkin's borrowed elements at face value as an artistic tool. They tend to draw attention to matters of the literary market and authorial propriety rather than to the borrowings' effects on the work. To go beyond such a perspective, this article proposes to do three interrelated things. First, Shishkin's so‐called plagiaristic method will be situated within the broader contexts of how contemporary Russian authors have used others' words, as well as of the history and theory of plagiarism. The second portion of this study will provide a typological analysis of Shishkin's borrowings and the intertextual play in which he engages: direct (or near direct) quotations; modified quotations; fragments; and paraphrasing. Finally, the various borrowings, drawn from both Western and Russian sources, serve to amplify Shishkin's thematics of identity. The novel itself, composed as it is in part of different voices, embodies a pressing need to find one's role in the contemporary world, where so much has already been said. Maidenhair is Shishkin's attempt to disrupt the notion of a stable, unified identity and, instead, to uphold the value of a blended identity that allows for links between disparate eras and peoples. As I will demonstrate, the borrowings contribute to and actualize these poetics and thematics by highlighting the recyclability of words, the universality of human experience and transformation, and the author‐creator's global perspective.